To rest or to compete? A 4-week cohort study of analgesic use and willingness to compete hurt in Danish youth elite athletes - Pedersen, J. R.; Møller, M.; Storm, L. K.; Koes, B.; Ntoumanis, N.; Thorlund, J. B. (Journal of Science and Medicine in Sport, 2023)
Objectives To assess the association between analgesic use and willingness to compete hurt (WCH) in Danish youth elite athletes, and to explore factors associated with such willingness.